Is the choice of a farm’s commercial market an indicator of agricultural intensity? Conventional and short food supply chains in periurban farming systems - Filippini, Rosalia; Marraccini, Elisa; Lardon, Sylvie; Bonari, Enrico (Italian Journal of Agronomy, 2016)
Short food supply chains (SFSCs) have been identified as an economic opportunity for agriculture under urban pressure, as well as drivers for more sustainable farming systems. However, few studies have focused on the intensity of periurban farms that participate in such SFSCs, compared with the performance of the other farms. In this paper, we examined the relationship between agricultural intensity and the market orientation in a representative sample of farms in the urban area of Pisa (Italy). We define agricultural intensity as the intensity of land use and its main drivers (e.g., farm management or the individual characteristics of farmers), and market orientation as the ratio of farm produce within conventional, short or mixed foodsupply chains. The results suggest that the market orientation of periurban farming systems is more correlated to the indicators of farm management and land use intensity than to the individual farmer’s characteristics. This result provides the first evidence that market orientation is a driver of intensity, and that individual farmer’s characteristics are not significantly different in the three groups of market orientation. These findings could be generalised to other urban areas and correlated with the main orientation of farming systems in order to support both the assessment of farming systems and the implementation of innovative urban food policies.